Introduction to the International Criminal Court - Schabas, William, 1950- (Cambridge, UK ; New York : Cambridge University Press, 2001)
"Arguably the most significant international organization to be created since the United Nations, the International Criminal Court ushers in a new era in the protection of human rights. The direct descendant of the Nuremberg and Tokyo trials, as well as those of the more recent international criminal tribunals for the former Yugoslavia and Rwanda, the International Criminal Court will prosecute genocide, crimes against humanity and war crimes when national justice systems are either unwilling or unable to do so themselves. This volume reviews the history of international criminal prosecution, the drafting of the Rome Statute of the International Criminal Court and the principles of its operation, including the scope of its jurisdiction and the procedural regime. The Court's fundamental documents - the Rome Statute itself, the Rules of Procedure and Evidence, and the Elements of Crimes - form an annex to the book."--Jacket.
Cover; Half-title; Title; Copyright; CONTENTS; PREFACE; ABBREVIATIONS; 1 Creation of the Court; 2 Crimes prosecuted by the Court; 3 Jurisdiction and admissibility; 4 General principles of criminal law; 5 Investigation and pre-trial procedure; 6 Trial and appeal; 7 Punishment and the rights of victims; 8 Structure and administration of the Court; Appendices; BIBLIOGRAPHY; INDEX.
Includes bibliographical references (pages 383-395) and index.
English.
Keywords: International Criminal Court; International Criminal Court; International criminal courts; Tribunaux criminels internationaux; Droit international pénal.; Law -- Criminal Law -- General; International criminal courts